(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: Characterize urinary incontinence (UI) prevalence and assess the quality of life (QoL) of women treated at a primary health care unit in order to compare the general QoL of continent and incontinent women. Methods: An exploratory-descriptive, cross-sectional pilot study with a quantitative approach. Sample composed of women over 18 years old who went to the unit for any reason. Data collection carried out from August to December 2021, through a standardized questionnaire with information on demographic, socioeconomic, obstetric, urinary habits and QoL. Results: Fifty-three women with a mean age of 44.49 (± 15.38) years participated. Most women declared themselves to be brown (62.3%), married or in a stable union (52.8%), exercising paid occupational activity (64.2%). As for urinary characteristics, 35.8% were diagnosed as incontinent, reporting that they lost urine once a week when they coughed or sneezed, and that this had a moderate impact on QoL. The differences in the values of QoL domains have a statistically significant correlation between the continent and incontinent groups. Conclusion: Urinary complaints prevail in a significant portion of women and UI is a factor capable of negatively impacting QoL, but it is necessary to prove the findings in a significant sample.